Construction of MMSN@Gem and its inhibition of proliferation and promotion of apoptosis in human bladder cancer cell line BIU-87 - WANG Daya, LI Zhijia, ZHAO Dewei, CHEN Ximeng (Jichu yixue yu linchuang, 2025)
Objective To prepare a multifunctional mesoporous silica-based nanocarrier system(MMSN@Gem) with gemcitabine and investigate its effect on bladder cancer cells BIU-87. Methods The multifunctional mesoporous silica-based nano drug-carrying system was prepared by a modified method. Transmission electron microscopy, high-performance liquid chromatography, and thermal imaging were used to characterize the morphology, drug-carrying and photothermal properties of MMSN@Gem. The effect of MMSN@Gem on BIU-87 bladder cancer cells was detected by in vitro experiments. Results MMSN@Gem exhibited a well-defined spherical morphology with an average particle size of(102.48±1.03)nm with a drug loading capacity of 25.04%±0.17%, and an average zeta potential of(-24.84±0.07)mV. The photothermal conversion efficiency was 40.7% which significantly enhanced the release of Gem under near-infrared irradiation. In vitro studies showed that MMSN@Gem significantly inhibited BIU-87 cell activity, induced apoptosis of BIU-87 cells, reduced migration and invasion ability, and enhanced its uptake by BIU-87 cells. Conclusions MMSN@Gem exhibits excellent photothermal properties, enhances cellular uptake efficiency, inhibits the proliferation and migration of BIU-87 cells, and promotes apoptosis, providing a promising drug delivery system for the clinical treatment of bladder cancer.